NARASI KHILAFAH DI ERA DIGITAL: Studi Epistemologi Muslimahnews.net atas Penafsiran Ayat Khilafah - Khairun Niam; Farida Nur Afifah (STAI AL-ANWAR SARANG, 2024)
Several Salafi Islamic organizations that openly campaign for the caliphate have begun to penetrate the realm of social media. One of them is in the Muslimahnews.com media which is allegedly managed by the HTI organization. Some of the writings in it echo the caliphate and kaffah Islam based on verses from the Koran and Hadith. Many of the contributors use classical interpretations and several opinions of prominent figures to strengthen the arguments built by them in campaigning for the caliphate and kaffah Islam. This research is included in a qualitative study using library research data collection techniques. The collected data was classified and analyzed using Abdul Mustaqim's epistemological theory. As for the results of this research, firstly , differences in views regarding the meaning of the caliphate are influenced by three things, namely the sources used, methodology and the validity of the truth to measure understanding regarding the caliphate. Second, Muslimahnews.com contributors tend to use textual methods in interpreting and analogizing their understanding, so that this understanding is not contextual to today's times